Evidence‐based therapy in hypertrophic scars: An update of a systematic review. Issue 5 (15th June 2020) - Nischwitz, Sebastian P.; Rauch, Katharina; Luze, Hanna; Hofmann, Elisabeth; Draschl, Alexander; Kotzbeck, Petra; Kamolz, Lars‐Peter
Abstract: Hypertrophic scars are still a major burden for numerous patients, especially after burns. Many treatment options are available; however, no evidence‐based treatment protocol is available with recommendations mostly emerging from experience or lower quality studies. This review serves to discuss the currently available literature. A systematic review was performed and the databases PubMed and Web of Science were searched for suitable publications. Only original articles in English that dealt with the treatment of hypertrophic scars in living humans were analyzed. Further, studies with a level of evidence lower than 1 as defined by the American Society of Plastic Surgeons were excluded. After duplicate exclusion, 1638 studies were screened. A qualitative assessment yielded 163 articles eligible for evidence grading. Finally nine studies were included. Four of them used intralesional injections, four topical therapeutics and one assessed the efficacy of CO2 ‐laser. Intralesional triamcinolone + fluorouracil injections, and topical pressure and/or silicone therapy revealed significant improvements in terms of scar height, pliability, and pigmentation. This systematic review showed that still few high‐quality studies exist to evaluate therapeutic means and their mechanisms for hypertrophic scars. Among these, most of them assessed the efficacy of intralesional triamcinolone injections with the same treatment protocol. Intralesional injection appears to be the best option for hypertrophic scar treatment. Future studies should focus on a possible optimization of infiltrative therapies, consistent end‐point evaluations, adequate follow‐up periods, and possibly intraindividual treatments.